The rose chafers (Coleoptera: Scarabaeidae: Cetoniinae) of Angola: a descriptive checklist with new records and synonymic notes - Serrano, Artur R. M.; Capela, Rúben A.; Nunes, Telmo; Santos, Carmen Van-Dúnem Neto (Zootaxa, 2020)
An annotated checklist of the species and subspecies of rose chafers (Scarabaeidae: Cetoniinae) hitherto known from Angola is given. This list includes species records from recent entomological trips in that country (2014, 2015 and 2017) and from Portuguese museums and private collections. A total of 177 species and 31 subspecies are recorded for Angola, including 32 endemic species/subspecies (15.4%). Some species are represented by only the holotype specimen (some without locality) or the type series. Others were recorded based on a single specimen. Records for four genera, one subgenus, twenty nine species and four subspecies previously unknown from Angola are given. A new synonymy is established: Ruteroides Gomes Alves, 1973 is proposed as a junior synonym of Pseudinca Kraatz, 1880. Consequently, Ruteroides fradei Gomes Alves, 1973 is transferred to Pseudinca. A brief historical review, as well as some considerations on the distribution and conservation status of these beetles in Angola is also presented.